A new species of myrmecophilous soft scale insect from Colombia in the genus Akermes Cockerell (Hemiptera: Coccoidea: Coccidae) - KONDO, TAKUMASA; WILLIAMS, MICHAEL (Revista Colombiana de Entomología, 2004)
A new species of myrmecophilous soft scale in the genus Akermes Cockerell, collected in Colombia, is described and illustrated. Information on distribution, host plants and morphological variation is given. This is the first record of the genus Akermes in Colombia.